A modified cyclic constitutive model for engineered cementitious composites. (15th January 2019) - Li, Xiaopeng; Zhou, Xiaoyong; Tian, Ying; Li, Mo
Highlights: A new cyclic constitutive model for ECC materials is proposed. The model improves the prediction of hysteretic stress-strain behavior of ECC. The model more accurately predicts residual deformation than existing models. The model is validated by experiments on various versions of ECCs and R/ECC. Abstract: Residual strain is a key parameter reflecting the damage condition of engineered cementitious composite (ECC) structural components after experiencing cyclic loads. A new cyclic constitutive model is proposed for ECC materials to accurately capture their hysteretic responses and residual strains for numerically simulating the seismic response of structural systems. Companion to the modeling, experiments were conducted on different versions of ECC with various mechanical properties, and on reinforced ECC specimens. The experimental data are used to calibrate and validate the proposed model. The discrepancies between the predicted and measured unloading residual deformations are found to be generally less than 6%.